2012
DOI: 10.1093/hmg/dds379
|View full text |Cite
|
Sign up to set email alerts
|

Selective histone deacetylase (HDAC) inhibition imparts beneficial effects in Huntington's disease mice: implications for the ubiquitin–proteasomal and autophagy systems

Abstract: We previously demonstrated that the histone deacetylase (HDAC) inhibitor, 4b, which preferentially targets HDAC1 and HDAC3, ameliorates Huntington's disease (HD)-related phenotypes in different HD model systems. In the current study, we investigated extensive behavioral and biological effects of 4b in N171-82Q transgenic mice and further explored potential molecular mechanisms of 4b action. We found that 4b significantly prevented body weight loss, improved several parameters of motor function and ameliorated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
95
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(101 citation statements)
references
References 47 publications
(54 reference statements)
6
95
0
Order By: Relevance
“…S2). These results are highly similar to our previous studies using HDACi 4b (9). However, we did not observe any significant transgenerational effects of RGFP966 on the F1 generation of N171-82Q transgenic mice (i.e., the offspring of RGFP966-treated fathers) (Fig.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…S2). These results are highly similar to our previous studies using HDACi 4b (9). However, we did not observe any significant transgenerational effects of RGFP966 on the F1 generation of N171-82Q transgenic mice (i.e., the offspring of RGFP966-treated fathers) (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Our studies have shown that inhibitors selectively targeting HDAC1 and HDAC3 are beneficial in several different HD model systems (9)(10)(11). In particular, in vivo studies have shown that pharmacological inhibition of HDAC1 and HDAC3 led to improved disease-associated body weight loss, motor dysfunction, and cognitive decline in two different HD mouse models (9,11). These findings are consistent with other studies showing beneficial effects of broadly acting HDAC inhibitors in HD mouse models (12)(13)(14).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…HDACi 4b treatment effectively restored acetylation of histone H3 and corrected mRNA expression levels in HD mice. HDACi 4b also significantly improved body weight and several parameters of motor function, and ameliorated cognitive decline in N171-82Q transgenic mice [101]. Interestingly, HDACi 4b treatment modulated gene networks involving post-translational modification, including protein phosphorylation and ubiquitination pathways.…”
Section: Hdac Inhibitorsmentioning
confidence: 91%
“…[5][6][7] The utility of HDACi in treating central nervous system (CNS) disorders is less clear; 8 however, abnormal expression levels of class-I HDACs have been correlated with several CNS disorders, including Huntington disease, 9 amyotrophic lateral sclerosis (ALS), [10][11][12] psychiatric disorders, 13 and Alzheimer disease.…”
Section: Class I Hdac Imaging Using [ 3 H]ci-994 Autoradiographymentioning
confidence: 99%